MILITARY FAMILIES SOCIETY TO ADAPT CHILD WITH LEADERSHIP QUALITY WITH PSYCHOLOGICAL AND PHYSICAL DEVELOPMENT - Haque Bhuiyan, Md. Majidul (International Journal of Engineering Technologies and Management Research, 2022)
Today’s Children’s are the leaders of future. To become a leader, balanced quality care process is in paramount requirement for children in a family. Caring of children has various dimensions like physical growth, mental growth etcetera. The ultimate aim is to become a good leader. As a requirement all families do care their children to become a good leader. Where Military families were prominent in the race. Military families have norms and traditions which leads the children to grow up. Military environment had also a significant role in children’s growing process. After the birth of Bangladesh children of military family led the society in all sector namely Government job, social affairs, society development, nation building even in international forum. Obviously business sector was not untouched after nineteen eighties nationally and internationally. The reason of doing well in all sector was, proper molding of military children’s as a leader. Even currently most of the sector has quality leaders, who have military background but not leading as it was in early Eighties and Nineties. Being a developing countries Bangladesh is in need of quality leaders.